Wilt Disease of Shisham (Dalbergia sissoo Roxb.) - Bakshi, B. K. (Indian Forester, 1957)
In vitro, Fusarium solani, causing wilt of shisham, is found to survive best in sterile loam soils containing up to 20 percent moisture. The pathogen however declines rapidly with the increase in moisture percentage in the soils above this level. This fact together with the circumstantial evidence that shisham thrives well in irrigated plantations free from root diseases suggest that the wilt diesase of shisham may be controlled in diseased areas by irrigation.